Calidad de los servicios de la compañía Rionet S.A. en la satisfacción de los clientes. Riobamba-Ecuador. - Guadalupe Castañeda, Viviana Jacqueline (2022)
Abstract The degree work, "Quality in the services of the company Rionet S.A. in customer's satisfaction. Riobamba-Ecuador", aims to analyze the quality of services to assess customers' satisfaction with the company Rionet. The elaboration is taken into account to carry out a trajectory of the different conceptualizations of quality and service, resulting in the global conceptualization of the quality of the service. For this reason, it is necessary to analyze the measurement model of the quality of the service as it is the SERVQUAL model, through it was possible to design the improvement plan for the quality of services and increase its impact on customers' satisfaction. To determine the validity of the variables, it was necessary to apply a suitable questionnaire for data collection and to be able to verify the hypothesis through the chi-square statistical test, generating an improvement plan so that the company can achieve a quality change in the service and obtain more possibilities of growth in the market.